2019
DOI: 10.3390/cancers11010088
|View full text |Cite
|
Sign up to set email alerts
|

The Opposing Contribution of SMS1 and SMS2 to Glioma Progression and Their Value in the Therapeutic Response to 2OHOA

Abstract: Background: 2-Hydroxyoleic acid (2OHOA) is particularly active against glioblastoma multiforme (GBM) and successfully finished a phase I/IIA trial in patients with glioma and other advanced solid tumors. However, its mechanism of action is not fully known. Methods: The relationship between SMS1 and SMS2 expressions (mRNA) and overall survival in 329 glioma patients was investigated, and so was the correlation between SMS expression and 2OHOA’s efficacy. The opposing role of SMS isoforms in 2OHOA’s mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 48 publications
0
26
1
Order By: Relevance
“…Fernández-García et al recently demonstrated through database analyses that glioblastoma multiforme patients with low SMS2 expression showed prolonged median survival compared patients with high SMS2 expression. 49 However, we could not find an association between SMS2 and ICAM-1 with poor prognostic lymphoma and infiltration from databases. One reason may be that these databases focus on the characterization of cancer cells but not on host cells associated with them.…”
Section: Discussioncontrasting
confidence: 63%
“…Fernández-García et al recently demonstrated through database analyses that glioblastoma multiforme patients with low SMS2 expression showed prolonged median survival compared patients with high SMS2 expression. 49 However, we could not find an association between SMS2 and ICAM-1 with poor prognostic lymphoma and infiltration from databases. One reason may be that these databases focus on the characterization of cancer cells but not on host cells associated with them.…”
Section: Discussioncontrasting
confidence: 63%
“…Oncology. The basis of developing MLT in oncology comes from the finding that membrane lipid composition might work as a switch allowing or compromising propagation of proliferation signals received at the PM in tumor cells [196,207]. Many molecules have been developed since the discovery membrane-altering mechanism of action of doxorubicin [199].…”
Section: New Lipid-based Therapeutic Avenues: Membrane Lipid Therapymentioning
confidence: 99%
“…EL4 injection increased ICAM-1 in the liver of WT mice but not in SMS2-KO mice. Moreover, a recent database analysis by Fernández-García et al 132 has demonstrated that SMS2 expression was low in glioblastoma multiforme patients, and was associated with prolonged median survival. Therefore, SM reduction by SMS2 inhibition could be a therapeutic target for the prevention of not only malignant lymphoma infiltration but also other cancers including glioblastoma.…”
Section: Phenotypes Of Smss-ko Mice In Disease Modelsmentioning
confidence: 99%